PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEIMIGRASIAN PENYIMPANAN DOKUMEN PALSU REPUBLIK INDONESIA (STUDI PUTUSAN 82/PID.SUS/2022/PN.JKT.PST): Enforcement of Law Against Persons of the Immigration Crime of Posting Fake Documents of the Republic of Indonesia (Decision Study 82/Pid.Sus/2022/PN.Jkt.Pst) - Zulpa, Novia Afri Kahtul; Sulistyowati, Tri (AMICUS CURIAE, 2024)
This research discusses the immigration crime of storing falsified Republic of Indonesia documents by Thevarajah Mathiraj, the law enforcement applied at the Central Jakarta District Court, and the preventative efforts from immigration authorities.  Research  Object,  Decision  Number 82/Pid.Sus/2022/Pn.Jkt.Pst. The research is normative juridically and descriptive in nature. The analysis uses secondary data and then analyzed qualitatively using deductive methods. The results of this research is the occurrence of an Immigration Crime was discovered after immigration officers received public reports or complaints of immigration violations committed by Thevarajah Mathiraj by keeping his KTP and Passport of the Republic of Indonesia while waiting to submit fake Republic of Indonesia documents to Jamil, an Indian citizen in the form of one Indonesian passport and one ID card in the name of Anthony Anadjeron which were forged. Therefore, Thevarajah Mathiraj violated Article 127 of Law Number 6 of 2011 concerning Immigration. The law enforcement applied in this case at the Central Jakarta district court was imprisonment for ten months and a fine of two hundred million rupiah. The preventative efforts made by the immigration authorities in dealing with this case are tightening the selection of foreigners, and Indonesian immigration permits domestically and abroad for foreigners.